Relegiusitas Yahweh Dalam Tranformasi Sistem Politik Israel Zaman PL - Sipora Blandina Warella (IAKN Ambon, 2018)
Confederation the tribes of Israel adopted the belief in Yahweh. This religiousitas have implication to politic sistem of Israel starting from the desert until Israel monarchy. Relegiousitas Yahweh appears on theocracy is take place in politic system, social, economy in Israel. This is make political system around the nation with Israel: Kings no no wrong, the King is god or son of god, system captalism and feudalism. Relegiousitas Yahweh has a power within the leadership of king of Israel economy, social revolution. But the transformation of Israel’s system into the same system with nation about getting noticed serius writers of The Old Testament, like writers Ur-Deuteronomy in Deuteronoy 17:14-20. The theory of the political system, David Easton is used in line with the contribution of the results of the hermeneutist text is the Israel political system must be fixed so that theocracy organization values living together can maintain the exixtence of Israel within the patern agrrement suzerain vassal.